FUNCTIONAL OUTCOME OF FRACTURE SHAFT OF FEMUR IN CHILDREN TREATED WITH EARLY HIP SPICA - Asghar Khan,; Mubashir Hassan,; Babar Shahzad Sadiq, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Femoral shaft fractures in children are a significant concern. Early hip spica casting is a treatment modality, but its functional outcomes need thorough evaluation. The objective of the study is to assess the functional outcomes of early hip spica management for femoral shaft fractures in children up to 5 years. Methods: A prospective observational study was conducted at Ayub Teaching Hospital from 15 January 2022 to 26 December 2022. Sixty-two children diagnosed with femoral shaft fractures and treated with early hip spica were enrolled. Exclusion criteria were defined. Functional outcomes, including limb shortening, malunion, skin breakdown, foot drop, and compartment syndrome, were evaluated. Follow-ups were scheduled at 6 weeks, 12 weeks, and 6 months. Data analysis was performed using SPSS software package 25. Results: Of the 45 patients analyzed, 75.56% were males. The average age was 3.56 years. Most fractures were proximal (75.55%) and resulted from motor vehicle accidents (66.67%). Limb shortening was observed in 17.77% of patients, with no significant correlation with age or fracture type. Malunion was rare (1%), and no skin breakdown, foot drop, or compartment syndrome cases were reported. Conclusion: Early hip spica casting for femoral shaft fractures in children up to 5 years is associated with minimal complications. The findings can guide clinical decisions and patient counselling.